Survival impact of pulmonary metastasectomy for patients with head and neck cancer. Issue 12 (6th March 2013) - Miyazaki, Takuya; Hasegawa, Yasuhisa; Hanai, Nobuhiro; Ozawa, Taijirou; Hirakawa, Hitoshi; Suzuki, Atsushi; Okamoto, Hiroki; Harata, Ikuma
<x xml:space="preserve">Abstract</x> Background The purpose of this study was to evaluate the survival impact and prognostic factors of pulmonary metastasectomy in patients with pulmonary metastasis from head and neck cancer. Methods A retrospective study of 69 patients was analyzed. Twenty‐four patients (35%) underwent pulmonary metastasectomy, and the remaining 45 patients (65%) were treated with chemotherapy or best supportive care. Results The 1‐year overall survival (OS) of 69 patients was 28%. Pulmonary metastasectomy (p = .01) and histology (p < .001) had a significant impact on the prognosis. One‐year OS of patients who underwent metastasectomy and those who did not was 90% and 35%, respectively. In the metastasectomy group, recurrence of primary ahead of lung metastasis (p = .006) and disease‐free interval (DFI; ≤21.4 months; p = .046) were significant negative prognostic factors. Conclusion Pulmonary metastasectomy has an impact on survival in carefully selected patients, especially for those with a long DFI and with no recurrence of primary cancer ahead of lung metastasis. © 2013 Wiley Periodicals, Inc. Head Neck 35: 1745–1751, 2012